2016
DOI: 10.3390/ma9110900
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Auxetic Cellular Material Consisting of Re-Entrant Hexagonal Honeycombs

Abstract: A preliminary study of the mechanical properties of auxetic cellular material consisting of re-entrant hexagonal honeycombs is presented. For different scales of the honeycombs, the finite element method (FEM) and experimental models are used to perform a parametric analysis on the effects of the Poisson’s ratio (cell angle) and the relative density (cell thickness) of honeycombs on bearing capacity and dynamic performance of the auxetic material. The analysis demonstrates that the ultimate bearing capacity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 29 publications
(34 reference statements)
1
31
0
Order By: Relevance
“…FEM and AM used in conjunction could facilitate such a parametric study with relative ease, for example by varying repeated structures [262]. AM structure's Poisson's ratio can be tuned by altering the geometry of a unit cell [263][264][265], enabling the design and analysis of novel auxetic structures using FEM [266,267] to help validate existing analytical formulae. Matlab has also been used to run FEM parametric analysis [167].…”
Section: Additively Manufactured Auxetic Materials and Structuresmentioning
confidence: 99%
“…FEM and AM used in conjunction could facilitate such a parametric study with relative ease, for example by varying repeated structures [262]. AM structure's Poisson's ratio can be tuned by altering the geometry of a unit cell [263][264][265], enabling the design and analysis of novel auxetic structures using FEM [266,267] to help validate existing analytical formulae. Matlab has also been used to run FEM parametric analysis [167].…”
Section: Additively Manufactured Auxetic Materials and Structuresmentioning
confidence: 99%
“…By comparing with honeycomb metamaterials by Zhang et al [ 43 ], the stiffness properties of the novel metamaterials are demonstrated. Comparison in Table 2 shows that the novel metamaterials exhibit higher specific stiffness values than honeycomb.…”
Section: Evaluation Methods Of Static Properties Of Metamaterialsmentioning
confidence: 99%
“…One such unique spatially arranged structure produces a negative Poisson's ratio (NPR); these are called auxetics. Similar to other types of mechanical metamaterials, the NPR of auxetics is generally a direct consequence of the topology, where the joints rotate to move the structure . This property of NPR materials makes them undergo volumetric expansion and contraction when they are stretched and compressed, respectively, allowing them to show compliant‐bending behavior.…”
Section: Introductionmentioning
confidence: 99%